2013
DOI: 10.1371/journal.pone.0073791
|View full text |Cite
|
Sign up to set email alerts
|

Personality, Gender, and Age in the Language of Social Media: The Open-Vocabulary Approach

Abstract: We analyzed 700 million words, phrases, and topic instances collected from the Facebook messages of 75,000 volunteers, who also took standard personality tests, and found striking variations in language with personality, gender, and age. In our open-vocabulary technique, the data itself drives a comprehensive exploration of language that distinguishes people, finding connections that are not captured with traditional closed-vocabulary word-category analyses. Our analyses shed new light on psychosocial processe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
1,210
4
29

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,342 publications
(1,332 citation statements)
references
References 72 publications
36
1,210
4
29
Order By: Relevance
“…It confirms Vingerhoets et al's (2013) conclusion of their overview of the psychological and neurological literature on swearing, namely that having an antisocial personality is linked to increased swearing (301). The effect of Psychoticism is also indirectly confirmed by the findings of Mehl et al (2006) and Schwartz et al (2013) whose participants scoring low on Agreeableness and Conscientiousness used more swearwords. The weaker effect of Psychoticism among LX users could be linked to their awareness that their pragmatic calibration might not have been precise enough to meet out the appropriate type and amount of swearwords which could have prompted violence in interactions with strangers.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…It confirms Vingerhoets et al's (2013) conclusion of their overview of the psychological and neurological literature on swearing, namely that having an antisocial personality is linked to increased swearing (301). The effect of Psychoticism is also indirectly confirmed by the findings of Mehl et al (2006) and Schwartz et al (2013) whose participants scoring low on Agreeableness and Conscientiousness used more swearwords. The weaker effect of Psychoticism among LX users could be linked to their awareness that their pragmatic calibration might not have been precise enough to meet out the appropriate type and amount of swearwords which could have prompted violence in interactions with strangers.…”
Section: Discussionsupporting
confidence: 60%
“…Extraversion could have a weaker effect for the L1 users as this identity issue does not apply to them. More neurotic, anxious individuals are more responsive to threat or stress which could translate in increased use of swearing, as Schwartz et al (2013) reported for Facebook updates. Interestingly, the effect was strongest for L1 users swearing with their friends and for LX users swearing when alone.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Sentiment analysis of social media data is becoming increasingly common (e.g., Schwartz et al, 2013), and could range from utilizing relatively simple pre-programmed psychological language dictionaries (e.g., Pennebaker, Chung, Ireland, Gonzales, & Booth, 2007), to complex machine learning/data-driven language categories (Eichstaedt et al, 2015).…”
Section: Social Media Analysismentioning
confidence: 99%
“…A data-driven approach might lead to an increased efficiency of text-based campaigns by being one step closer to delivering "the right offer to the right customer". For example, previous research showed that data-driven approaches can reliably predict mobile phone and Facebook user's personality [3][4][5]18], sexual orientation [6], or romantic relationships [7].…”
Section: Introductionmentioning
confidence: 99%